(untitled) (ModaPalavra e-periódico, 2024)
The article examines the changes in representations of masculinities in fashion editorial photographs from 2015 and 2023, using discourse analysis (Bardin, 1977) on editorials from the Fucking Young! platform/magazine. A total of 274 editorials from 2015 and three from 2023 were analyzed. The results showed evolutions in the representations, with an emphasis on sports practices, celebration of a healthy body, and connection with nature, challenging gender paradigms. However, a preference for white-skinned models persists, marginalizing those with black skin. It is concluded that male representations are undergoing transformation, reflecting cultural changes. Despite progress, there are challenges in promoting a more inclusive and diverse representation. The study is a partial result, suggesting future research to better understand these changes over time.